The Expression of Christian Values at Music Lessons: the Analysis of Textbooks of 1–4 Grades - Kauneckas, Klaidas (Jaunųjų mokslininkų darbai, 2022)
The article examines primary school textbooks by different authors, using the content analysis method. The goal was to reveal how often and in what way the Christian values are cultivated through the content of the music education. The results of the examination revealed that in a music textbook “Vieversys” the most attention is given to the folklore, secularism and culture; the textbook “Lakstute” gives an opportunity to the teacher to emphasize Christian values by accentuating topics of Christmas and Easter. The textbooks “Mano Muzika” focus not only on cherishing nationality, expressing knowledge of music from different nations, but also present Christian celebrations in detail.
Keywords: Christian values; music lesson; textbooks for 1–4 grades